Contemporary Dronosphere. Socialization and Learning in a Global ?Culture of Sensors? - Bougsiaa, Hussein; Kopciewicz, Lucyna; Nowicki, Tomasz (INSTED: Interdisciplinary Studies in Education & Society, 2016)
This article explores the figure of the drone and the emerging logics of the ubiquitous, always-on sensor-based monitoring. The arguments presented in the article are not exclusively about drones, but about what is described as ?drone logic?: the deployment of ubiquitous, always-on networked sensors for the purposes of automated data collection, processing and response. We examine the social implications of the process which might be called the ?droning? of daily interactions across various spheres of social practices such as learning, entertainment, socialization and identity construction. This article offers an insight into the military-inflected rationality of globalization, everydayness and contemporary culture.